Exploiting Cross-Luminescence in BaF2 for Ultrafast Timing Applications Using Deep-Ultraviolet Sensitive HPK Silicon Photomultipliers - Pots, Rosalinde Hendrika; Auffray, Etiennette; Gundacker, Stefan (Frontiers in Physics, 2020)
Time resolution of scintillation-based detectors is becoming continuously more important, both for medical applications, especially in positron emission tomography (PET), and in high energy physics. This article is an initial study on exploiting the fast cross-luminescence emission in the inorganic BaF2 scintillator with deep ultraviolet-sensitive silicon photomultipliers (SiPMs) from Hamamatsu for precise timing in PET and HEP. Using small BaF2 pixels optimized for timing read out by these photodetectors with a photon detection efficiency (PDE) of only about 15% in the desired 200 nm emission region, a coincidence time resolution (CTR) of 94 ± 5 ps full width at half maximum (FWHM) is achieved when coupling with air. This figure improves to 78 ± 4 ps FWHM when coupling the BaF2 crystal with UV transparent optical grease, Viscasil, to the photodetector. This CTR performance obtained with BaF2 is better than that measured with LYSO:Ce, a commonly used state-of-the-art inorganic scintillator in PET, when coupled to another Hamamatsu photodetector (S13360), having a PDE of 60% at 420 nm, with Meltmount. In view of the prospects in advancing technologies for ultraviolet sensitive SiPMs, with high PDE and single photon time resolution, and further advancements in producing high quality BaF2, one could imagine the development of sub-30 ps FWHM time-of-flight-PET systems.